2014
DOI: 10.2139/ssrn.2536794
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Virtual Water Flows in the Mediterranean

Abstract: The aim of the paper is to investigate the main determinants of the bilateral virtual water 'flows' associated with international trade in agricultural goods across the Mediterranean basin. Virtual water refers to the volume of water used in the production of a commodity or a service. The exchange of water as embedded in traded goods brings about the so-called virtual water 'trade'. We consider the bilateral gross 'flows' of virtual water in the area and study what export-specific and import-specific factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…The finding that GDP, population and irrigated land are significant in explaining NVWI dynamics supports the results of Tamea et al (2014), who studied the drivers of virtual water trade using gravity laws. The finding that blue water scarcity was not an influencing factor of virtual water trade in a water-scarce country is similar to the finding of Kumar and Singh (2005) and Fracasso et al (2016), who found that water endowment and water scarcity were not driving factors for virtual water trade for specific countries. However, blue water scarcity may have indirectly influenced the temporal development of the irrigated area that was identified as a significant factor to explain net virtual water import for some crops.…”
Section: Refection On Research Findings and Contributions To Scientifsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding that GDP, population and irrigated land are significant in explaining NVWI dynamics supports the results of Tamea et al (2014), who studied the drivers of virtual water trade using gravity laws. The finding that blue water scarcity was not an influencing factor of virtual water trade in a water-scarce country is similar to the finding of Kumar and Singh (2005) and Fracasso et al (2016), who found that water endowment and water scarcity were not driving factors for virtual water trade for specific countries. However, blue water scarcity may have indirectly influenced the temporal development of the irrigated area that was identified as a significant factor to explain net virtual water import for some crops.…”
Section: Refection On Research Findings and Contributions To Scientifsupporting
confidence: 86%
“…They found that GDP and distance are the fundamental controlling factors of virtual water trade, both for import and for export, while the arable land does not give a significant contribution. In a more recent study, Fracasso et al (2016) investigate the determinants of the bilateral virtual water trade in the Mediterranean basin. The study showed that larger water endowments do not necessarily lead to larger export of water-intensive products.…”
Section: Introductionmentioning
confidence: 99%
“…Fracasso (2014) estimates a trade gravity mo del and finds that bilateral flows are affected by water endowments and pressure on water resources in addition to the classic determinants of the gravity model. Utilizing the same model, and examining VW flows across the Mediterranean basin, Fracasso et al (2016) verify that larger water endowments do not necessarily result in more VW exports. Seekell et al (2011) use trade data to argue that VW flows are directed by global economic structures and trade relations rather than by the relative scarcity of water within nations.…”
Section: Introductionmentioning
confidence: 91%
“…Agricultural irrigation has a large water demand, while service industries need less water. Much research has been done on virtual water trade for relieving water stress [32][33][34][35]. However, the application of virtual water strategies to improve water use efficiency was challenged due to comprehensive capacities of economic level, social equity, infrastructural construction, and potential eco-environmental effect.…”
Section: Water Stress and Virtual Water Strategymentioning
confidence: 99%